Specificity of characteristic marks on cartridge cases from 3070 consecutive firings of a Chinese Norinco QSZ-92 9 mm Pistol - Feng Dong; Yabin Zhao; Yaping Luo; Weifang Zhang; Kaifeng Zhang (Wolters Kluwer Medknow Publications, 2019)
The specificity of marks was evaluated by differences between marks left by the same firearm (within variability) and differences between marks left by different firearms (between variability). The within variability and between variability of firing pin impressions and breech face marks on cartridge cases from over 3070 consecutive firings of a Chinese Norinco QSZ-92 9 mm pistol were investigated based on the automated ballistic identification system Evofinder®. The first 20 cartridge cases and one random specimen out of every set of 10 consecutive cartridge cases of the remaining 3050 cases were entered into the Evofinder® system. Thus, 325 cartridges fired from the same pistol were used to estimate the within variability. Then, 88 cartridges fired from 88 different pistols of the same model (one cartridge each) were used to estimate the between variability. This study established a database containing 413 cartridges. We used the 325 cartridges fired from the same pistol as a correlation baseline in the database. Both firing pin and breech scores and gaps between these scores were used to analyze the variability. In the score evaluation process, a likelihood ratio system was used to evaluate the likelihood ratio performance. The Evofinder® system correctly discriminated the matches, and the likelihood ratios provided strong support for the true state of the hypothesis. In addition, we found that the score gap was usually greater than the other score differences by more than 1000% in firing pin list and 100% in the breech list. Further analysis of the score and gap can help examiners use the Evofinder® system more efficiently.